Computational analysis and comparison of reversible gates for design and test of logic circuits. Issue 11 (2nd November 2019) - Gaur, H. M.; Singh, A. K.; Mohan, A.; Pradhan, D. K.
ABSTRACT: Quantum computing is one of the most significant anticipation towards the accomplishment of interminable consumer demands of small, high speed, and low-power operable electronics devices. As reversible logic circuits have direct applicability to quantum circuits, design and synthesis of these circuits are finding grounds for emerging nano-technologies of quantum computing. Multiple Controlled Toffoli (MCT) and Multiple Controlled Fredkin (MCF) are the fundamental reversible gates that playing key role in this phase of development. A number of special reversible gates have also been presented so far, which were claimed superior for providing certain purposes like logic development and testing. This paper critically analyses a range of these gates to procure an optimal solution for design, synthesis and testing of reversible circuits. The experimentation is facilitated at three subsequent levels, i.e. gates properties, quantum cost and design & testability. MCT and MCF gates are found up to 50% more cost-effective than special gates at design level and 34.4% at testability level. Maximum reversibility depth (MRD) is included as a new measurement parameter for comparison. Special gates exhibit MRD up to 7 which ideally should be 1 for a system to be physically reversible as that of MCT and MCF gates.